Sebuah Laporan Kasus Anemia Hemolitik Autoimun dengan Trombosis Vena Dalam pada Gadis 16 Tahun - Apakah Lupus Eritematosus Sistemik? Laporan Kasus - Buchori, Muhammad; Joalsen Mangaratua, Ivan; Corona, Fidel; Sanjaya, Kevin; Mulyani, Laily (Cermin Dunia Kedokteran, 2025)
Introduction: Systemic lupus erythematosus (SLE) is an autoimmune disease with various clinical manifestations. Multiorgan involvement is associated with a worse prognosis. SLE in pediatrics is rare, with an estimated incidence of 0.3–0.9 per 100,000 children. Case: A 16-year-old Asian girl was admitted with pain, swelling, and a bluish discoloration with blisters on the right leg for 6 days. She had a history of facial rash, hair loss, and oral ulcer. Doppler ultrasound showed deep vein thrombosis in the right lower extremity with acute thrombosis, with visible soft-material intraluminal thrombus. Coombs test was 4+ positive. Elevated total bilirubin 2.2 mg/dL, indirect bilirubin 0.9 mg/dL, and elevated reticulocyte 5.2%. ANA test result is borderline 0.8, and anti-DS DNA negative. CT angiography showed proximal total occlusion of the right dorsalis pedis artery, DVT along the external iliac vein, femoral vein, and popliteal vein to the proximal 1/3 of the right posterior tibial vein. Diagnosis of an autoimmune disease leading to autoimmune hemolytic anemia and deep vein thrombosis was suspected. Her condition improved after corticosteroids and anticoagulant treatment. Conclusion: A 16-year-old girl was diagnosed with autoimmune hemolytic anemia, deep vein thrombosis, and suspected systemic lupus erythematosus. Early recognition of unusual manifestations of SLE is important.